From supratidal to subtidal, an integrated characterisation of Carbla Beach shallow microbial mats (Hamelin Pool, Shark Bay, WA): Lipid biomarkers, stable carbon isotopes and microfabrics - Plet, Chloe; Pagès, A.; Holman, Alex; Madden, Robert; Grice, Kliti (Elsevier Science BV, 2018)
Modern microbial mats from Shark Bay are commonly regarded as robust analogues for Precambrian stromatolites. These microbial mats are complex ecosystems that exhibit intense biogeochemical recycling. In this study, a multi-proxy approach (including lipids, compound-specific carbon isotope analysis and petrography) is used to characterise microbial communities in three different types of mats (tufted, pustular and smooth) along the shallowest section of a tidal flat gradient. Cyanobacterial lipids were present in all three mats. Petrographical (optical and scanning electron microscopy) investigations also revealed that ooids in the tufted mat were larger and more common compared to the pustular and smooth mats. Biomarkers specific to sulfate reducing bacteria were detected in all mats. The diatom-specific C25:1highly branched isoprenoid (HBI) alkene was most abundant in the smooth mat. However, imaging revealed that the smooth mat only contained rare diatoms of small size (~10 µm), whereas the pustular mat contained a variety of larger diatoms (~50 µm). The C25:1HBI alkene marker is only produced by four diatom genera, which were most likely more represented in the smooth mat. Additionally, the smooth mat contained a greater contribution from aquatic macrophytes (Paq = 0.38) compared to the shallower mats, which is corroborated by the presence of13C-enriched seagrass lipids (i.e. C29steradiene). In all the mats, a major eukaryotic contribution was revealed via imaging techniques and supported by a high sterol content. This eukaryotic component (e.g. benthic foraminifera, diatoms) can impact the cohesive structure of the mats, the lithification processes and the lipid distribution, potentially complicating comparisons with Precambrian microbialites that were not affected by eukaryotic activity. This study reemphasizes the complexity of microbial ecosystems, and therefore highlights the benefit of multi-proxy approaches to characterise these biological systems.